Evaluation of Daily CT for EPID-Based Transit In Vivo Dosimetry - Feng, Bin; Yu, Lei; Mo, Enwei; Chen, Liyuan; Zhao, Jun; Wang, Jiazhou; Hu, Weigang (Frontiers in Oncology, 2021)
Purpose: The difference in anatomical structure and positioning between planning and treatment may lead to bias in electronic portal image device (EPID)-based in vivo dosimetry calculations. The purpose of this study was to use daily CT(dCT) instead of planning CT(pCT) as a reference for EPID-based in vivo dosimetry calculations and to analyze the necessity of using daily CT for EPID-based in vivo dosimetry calculations in terms of patient quality assurance. Materials and methods: Twenty patients were enrolled in this study. The study design included 8 different sites (the cervical, nasopharyngeal and oral cavities, etc). All treatments were delivered with a CT-linac 506c using 6 MV photon beams. A pretreatment measurement was performed to assess system accuracy by delivering based on a homogeneous phantom. During treatment, each patient underwent CT scanning before delivery either once or twice, for a total of 268 fractions obtained dCT images. Patients may have had a position correction that followed our IGRT procedure. Meanwhile, transmit EPID images were acquired for each field during delivery. The reference of transmit EPID images was calculated based on both pCTs and dCTs. The gamma passing rate was calculated and compared between the pCT and dCT. Mechanical errors were also introduced in this study for comparing detectability between both types of CT. Result: The average (standard deviation) gamma passing rate (3 mm 3%, 2 mm 3%, and 2 mm 2%) in the phantom was 99.6%±1.0%, 98.9%±2.1%, and 97.2%±3.9%. For patient measurement, the average gamma passing rates were 87.8%±14.0%, 82.2%±16.9% and 74.2%±18.9% for using pCTs as reference and 93.6%±8.2%, 89.7%±11.0% and 82.8%±14.7% for using dCTs as reference. In terms of error simulation. The ROC analysis indicated that the detectability of mechanical delivery error using dCT better than pCT. AUC(dCT)=0.63-0.96 and AUC(pCT)=0.49-0.93 in MLC systematic shift and AUC(dCT)=0.56-0.82 and AUC(pCT)=0.45-0.73 in MU scaling. Conclusion: This study shows the feasibility and effectiveness of using 2D EPID portal image and daily CT-based in vivo dosimetry for verification during treatment. The daily CT-based in vivo dosimetry has better sensitivity and specificity to identify the variation in MLC-related and dose-related errors than planning CT-based.